KONSERVASI HUTAN PADA JURNAL BIOLOGI INDONESIA PERIODE 2010-2020: SEBUAH STUDI BIBLIOMETRIK - Yupi Royani; Rochani Nani Rahayu (Perpustakaan Nasional RI, 2021)
A bibliometric analysis was carried out on the Indonesian Biology Journal for the period 2010 – 2020, with the aim of knowing 1) the distribution of keywords to see the description of the research published in the Indonesian Biology Journal 2010-2020; 2) article classification; 3) distribution of articles by year; 4) distribution of articles by issue number; 5) authorship pattern; 6) the most prolific writer; 7) affiliations of authors who contribute to the Indonesian Biology Journal; 8) the type of document used as a reference in the Indonesian Biology Journal 2010-2020. The bibliometric method was used, and the data was taken from the Indonesian Biology Journal from 2010 to 2020, which was downloaded via the address https://e-journal.biologi.lipi.go.id/index.php/jurnal_biologi_indonesia. Furthermore, the analysis of the distribution of articles based on keywords, distribution of class numbers, distribution of articles by year, distribution of articles by number of publications, pattern of authorship, most productive authors, pattern of authorship affiliation was carried out. Based on the results and discussion, it can be concluded that during 2010-2020, 315 article titles have been published and there are 1,343 keywords. Of the 50 most keywords, the keyword Biodiversity often appears 21 times (1.56%) then Genetic variation and Wildlife conservation each 20 times (1.48%), then Animal population 18 times (1.34 %), followed by Plant conservation 17 times (1.19%) and Animal conservation 16 times (1.19%). Next is Feeds and Plant growth substances each with 15 (1.11%), then In vitro culture and Plant diversity each with 14 (1.04%). Next, Vegetation is 13 (0.90%), followed by Habitat conservation and Plant species, each with 11 (0.82%). On the order of 50 keywords Drought resistance, with a total of 4 (0.29%). The highest class is class 635 with a frequency of 35 (11.11%). Articles written by a single author (71 titles; 22.54%) and articles written by collaboration (244 titles; 77.46%). the least number of articles published is in 2020, which is 1 article title (3,17). For issue number 1 starting from volume 6 to volume 16, 164 article titles have been published (52.06%). As for number 2 with the same volume, there were 151 article titles (47.94%). The most prolific writer is Hellen Kurniati with 13 writings, followed by Wartika Rosa Farida with 12 writings and then Witjaksono with 11 writings. Then Andri Permata Sari, Niken Tunjung Murti Pratiwi, NLP. Indi Dharmayanti, Tri Muji Ermayanti with 10 each, followed by Didik Widyatmoko and Risa Indriani with 9 each, Atit Kanti and Yopi with 7 each and Dwi Astuti, Eko Sulistyadi, Ibnu Maryanto, Inna Puspa Ayu each. 6 posts. LIPI is the first institution that contributes the most articles, with a frequency of 260 times. It is known that 7,354 document titles are used as references and the journal is in the first order of cited documents, with 4,591 titles (62.42%).